1991
DOI: 10.1037/0033-2909.110.1.109
|View full text |Cite
|
Sign up to set email alerts
|

What is beautiful is good, but…: A meta-analytic review of research on the physical attractiveness stereotype.

Abstract: This review demonstrates that the physical attractiveness stereotype established by studies of person perception is not as strong or general as suggested by the often-used summary phrase what is beautiful is good. Although subjects in these studies ascribed more favorable personality traits and more successful life outcomes to attractive than unattractive targets, the average magnitude of this beauty-is-good effect was moderate, and the strength of the effect varied considerably from study to study Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

78
1,076
12
41

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,522 publications
(1,207 citation statements)
references
References 136 publications
78
1,076
12
41
Order By: Relevance
“…However, the studies included in his 1990 meta-analysis were virtually identical to those included in Feingold (1992b) and are therefore not cited here as a third meta-analysis. Barber, 1995;Berscheid & Walster, 1974;Buss, 1998Buss, , 1999Buss & Schmitt, 1993;Cunningham, Druen, & Barbee, 1997;Eagly et al, 1991;Feingold, 1992a;L. A. Jackson, 1992;D.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies included in his 1990 meta-analysis were virtually identical to those included in Feingold (1992b) and are therefore not cited here as a third meta-analysis. Barber, 1995;Berscheid & Walster, 1974;Buss, 1998Buss, , 1999Buss & Schmitt, 1993;Cunningham, Druen, & Barbee, 1997;Eagly et al, 1991;Feingold, 1992a;L. A. Jackson, 1992;D.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…Like the stranger-attribution research reviewed by Eagly et al (1991), most of the research we reviewed categorized people into two levels of attractiveness, high or low. Even after reviewing over 900 effect sizes, we can conclude only that attractive and unattractive individuals are different in how they are judged, how they are treated, and how they behave.…”
Section: Limiiationsmentioning
confidence: 99%
“…Several studies have identified distinct economic advantages to being attractive (Dion, Berscheid, & Walster, 1972;Eagly, Ashmore, Makhijani, & Longo, 1991;Hatfield & Sprecher, 1986). In particular, attractive people generally fare better in the labor market.…”
Section: Physical Attractiveness and Labor Marketsmentioning
confidence: 99%
“…Em concordância com Eagly et al (1991) que desenvolveram um estudo de metaanálise destacando que a força da atratividade física sobre os julgamentos e expectativas não seria universal e tão intensa como advogam inúmeras pesquisas sobre estereótipos, tratando-se sempre de uma questão relativa e suscetível a inúmeras circunstâncias e fatores.…”
Section: Percepções Sobre Pessoas Com Deficiênciasunclassified